If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1d = d + -6 Reorder the terms: 8 + -1d = -6 + d Solving 8 + -1d = -6 + d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 8 + -1d + -1d = -6 + d + -1d Combine like terms: -1d + -1d = -2d 8 + -2d = -6 + d + -1d Combine like terms: d + -1d = 0 8 + -2d = -6 + 0 8 + -2d = -6 Add '-8' to each side of the equation. 8 + -8 + -2d = -6 + -8 Combine like terms: 8 + -8 = 0 0 + -2d = -6 + -8 -2d = -6 + -8 Combine like terms: -6 + -8 = -14 -2d = -14 Divide each side by '-2'. d = 7 Simplifying d = 7
| 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 | | 0=1.5x-3.4 | | 2(710+1)= | | 3(-8+8x)=-192 | | (x-2)(x^2-2x+4)-x(x-3)(x+3)=26 | | 5q+-6q-p= | | 1410+2= | | 5(2t+3)=30-5t | | 0=9x^2+12x-3 | | 5x+23=x+3 | | g(5+7)= | | 3x-8=8x+6 | | log(3)0.63= | | 2(14+w)=52 | | =.5x^2-4x+12 | | -2z+3+3+7z=-12 | | 4msquared-24+36=0 |